Nilai-Nilai Moral pada Cerita Rakyat Desa Rantau Kalis dan Implementasi di SMA Karya Budi - Adriana, Betania Clara; Thamimi, Muhammad; Sulastri, Saptiana (Journal of Multidiscipline and Collaboration Research, 2024)
This research describes the moral values in the folk tales of Rantau Kalis Village and their implementation in Indonesian language learning at Karya Budi High School, Kapuas Hulu Regency. This study uses a descriptive qualitative method with a sociological literature approach. Data were collected through direct communication, recording, observation, and documentary study techniques, using interview guides, recording devices, observation guides, and the researcher as the instrument. The results of the study show that moral values related to God are found in the stories "Liakung," "Bararu," and "Batu Rabor." Moral values related to oneself are found in "Liakung," "Tau Masek-Masek," "Bararu," "Batu Rabor," and "Mantusan Tampurung Amas." Moral values related to fellow humans are found in "Baling Bunga dan Bunga Lita," "Tau Masek-Masek," "Batu Rabor," "Bararu," "Liakung," and "Bintang Talu." The implementation of learning at Karya Budi High School has been well executed, with students able to find implicit and explicit meanings in the folk tales, as evidenced by their assignments. These moral values help shape better student character. Additionally, folk tale-based learning makes students more interested and motivated in learning.